2013
DOI: 10.2355/isijinternational.53.782
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mathematical Models of Vortex Flows During The Last Stages of Steel Draining Operations from a Ladle

Abstract: Slag entrainment during steel teeming-drain operations from a steel ladle impacts negatively steel cleanliness and quality. In the present work water modeling and mathematical simulations using a multiphase model for momentum and heat transfer were employed to understand the mechanisms of vortex funnel drain and sink drain flows. The critical bath height for vortex development increases with steel throughput and valve gate opening. Six stages during vortex development are identified, passing from a dimple form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Following partial results of works [8][9][10][11][12][13][14][15][16] a trend was found to increase the critical level with the application of liquid with lower density.…”
Section: Study Of Tundish Slag Entrainment Using Physical Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Following partial results of works [8][9][10][11][12][13][14][15][16] a trend was found to increase the critical level with the application of liquid with lower density.…”
Section: Study Of Tundish Slag Entrainment Using Physical Modellingmentioning
confidence: 99%
“…Critical levels for vortex creation were compared and discussed in the paper [14]. when the paraffin oil was applied, the critical level for vortex creation was at the height of 191 mm, when paraffin oil with low viscosity was used, then the height was 195 mm.…”
Section: Study Of Tundish Slag Entrainment Using Physical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hammerschmid et al [1] and Andrzejewski et al [6] reported that the vortex formation depends strongly on the state of initial rotation. However, Morales et al [7] and Dubke et al [8] reported that the initial rotation had little or null influence on the vortex formation. The vortex formation is also affected by the eccentricity of the draining nozzle [1,4,9,10], the steel throughput [5,11], the slag thickness [12,13], the ratios of viscosity as well as density between steel and slag [14], the diameter ratio of the outlet nozzle and the ladle [2,15], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A drain sink is always present at the end of the process and takes place when the bath height of the steel is approximately equal to the nozzle diameter [4,6,16]. Several researchers claim that there was no vortex formation and slag carry-over was caused by drain sink in the teeming ladle [4,8], while more researchers reported that vortex was formed prior to the drain sink formation [1][2][3]7,17].…”
Section: Introductionmentioning
confidence: 99%